2018
DOI: 10.1029/2018jb016214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fault Roughness on Aftershock Distribution: Elastic Off‐Fault Material Properties

Abstract: We perform physics‐based simulations of earthquake rupture propagation on geometrically complex strike‐slip faults to examine the off‐fault stress changes resulting from dynamic fault slip. We consider many different realizations of the fault profile and use the output of our simulations to calculate the Coulomb failure function (CFF) for each realization. We analyze the effects of fault maturity as well as the self‐affine character of the fault surface on the stress field. To quantify our results, we calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 145 publications
5
21
0
Order By: Relevance
“…They find that the width of this near-fault region of high stresses is insensitive to H but decreases with γ. Assuming that our observed shear deformation zone represents the nearfault region of high stresses, this suggests that the observed decrease of W S2 with fault displacement is the result of smoothing of the fault with slip, similarly to observations made during laboratory experiments (Goebel et al, 2017) Aslam and Daub (2018) found that the half-width of the near-fault zone W nf is ∼2.7 and ∼0.9 km for profiles with fault roughness RMS values γ of 0.01 and 0.001, respectively. Comparing these results with the range of W S2 in Figure 5 indicates that more than an order of magnitude of roughness change will be required to explain these observations.…”
Section: The Nature Of the Shear Deformation Zone And The Smoothing Of Faultssupporting
confidence: 85%
See 1 more Smart Citation
“…They find that the width of this near-fault region of high stresses is insensitive to H but decreases with γ. Assuming that our observed shear deformation zone represents the nearfault region of high stresses, this suggests that the observed decrease of W S2 with fault displacement is the result of smoothing of the fault with slip, similarly to observations made during laboratory experiments (Goebel et al, 2017) Aslam and Daub (2018) found that the half-width of the near-fault zone W nf is ∼2.7 and ∼0.9 km for profiles with fault roughness RMS values γ of 0.01 and 0.001, respectively. Comparing these results with the range of W S2 in Figure 5 indicates that more than an order of magnitude of roughness change will be required to explain these observations.…”
Section: The Nature Of the Shear Deformation Zone And The Smoothing Of Faultssupporting
confidence: 85%
“…This is a much higher rate of smoothing than that of individual fault segment surfaces, and is comparable to that we infer from the narrowing of the shear deformation zone. Converting the roughness parameter step frequency of Stirling et al (1996) to γ using the typical step width 1-2 km (Wesnousky, 1988) and their smoothing curve allows us to recast the two fiducial points of Aslam and Daub (2018) from (W nf , γ) to (W nf , D) coordinates (i.e., γ values of 0.001 and 0.01 corresponding to fault displacements "D" of 100 and 10 km, respectively). These are plotted in Figure 7 (blue circles) where they are compared with our W S2 measurements from Figure 5b (squares).…”
Section: The Nature Of the Shear Deformation Zone And The Smoothing Of Faultsmentioning
confidence: 99%
“…To illustrate its effect, we plot the distribution of aftershocks for different aspect ratios α in Equation 1 in Figure 6. The number of fault‐side aftershocks increases with fault roughness because of the increase in positive Δ CFF area (Aslam & Daub, 2018; Smith & Dieterich, 2010), where the positive stress perturbation due to roughness overcomes the overall decreasing trend in the stress shadow.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we find that fault-side aftershocks include few large events (>10 −3.5 in the normalized seismic moment), whereas fault-tip events include large events. This is because fault-side aftershocks occur in a highly heterogeneous stress field and the rupture easily stops in regions where ΔCFF is negative (Aslam & Daub, 2018). In contrast, fault-tip aftershocks have the potential to grow large because ΔCFF is uniformly positive.…”
Section: Magnitude Distribution Of Aftershocksmentioning
confidence: 99%
See 1 more Smart Citation